Molecular Pathology of Endocrine Diseases - Hunt, Jennifer L. (Molecular Pathology Library, 2010)
The Molecular Pathology Library Series fills the gap between basic science and clinical application. Each user-friendly reference brings together diverse topics about molecular pathogenesis, diagnosis and treatment in one volume. The series serves physicians and healthcare providers in multiple disciplines who need to understand and apply molecular diagnostics and therapy to patient care; residents and fellows who integrate molecular medicine into their curricula and future practice; and basic and translational researchers who must define the impact of their research on clinical medicine.